LINE-1 hypomethylation is associated to specific clinico-pathological features in Stage I non-small cell lung cancer. (June 2017) - Imperatori, Andrea; Sahnane, Nora; Rotolo, Nicola; Franzi, Francesca; Nardecchia, Elisa; Libera, Laura; Romualdi, Chiara; Cattoni, Maria; Sessa, Fausto; Dominioni, Lorenzo; Furlan, Daniela
Highlights: The vast majority of stage I NSCLCs harbour at least one driver gene alteration. Druggable mutations are present in stage I NSCLC. LINE-1 hypomethylation is a striking feature of SqCC and correlates with smoking. Stage IB, LINE-1 hypomethylation, and PIK3CA mutations could predict patient prognosis. Abstract: Objectives: We hypothesize that selected genetic and/or epigenetic changes associated with advanced tumours may help identifying early non-small cell lung cancers (NSCLCs) that recur after resection. Among epigenetic changes, long interspersed nuclear element-1 (LINE-1) hypomethylation is seen early during carcinogenesis and may act in concert with genetic alterations to cancer progression. LINE-1 hypomethylation and gene mutations frequently involved in lung cancer, were analysed to evaluate their prognostic role in resected stage I NSCLC. Methods: Gene mutations and LINE-1 methylation were analysed in 167 Caucasian patients with stage I NSCLC, namely 100 adenocarcinomas (ADC) and 67 squamous-cell carcinomas (SqCC), using mass-spectrometry and pyrosequencing. We evaluated the correlation between molecular results and clinico-pathological data: age, gender, smoking status, period of surgery, histology, grading, pathological stage, p53 expression, LINE-1 hypomethylation. These variables have been assessed as possible predictors of cancer related survival by regression analysis. Results: Frequency and spectrum of gene mutations were significantly different in ADCs compared with SqCCs. p53 positivity was more common in SqCC, while EGFR or KRAS mutations were mainly detected in ADC. LINE1 hypomethylation was associated with SqCC histology, p53 immunoreactivity and smoking habit. Stage IB, LINE-1 hypomethylation and PIK3CA mutation independently predicted a worse cancer-related survival. When combined into a scoring system, their prognostic power was strengthened. Conclusions: In many stage I NSCLC a mutation pattern of advanced disease was observed. Stage IB, LINE-1 hypomethylation and PIK3CA mutation were associated to poor prognosis. Genetic and epigenetic events occurring in early carcinogenesis may help identifying stage I NSCLC patients who deserve adjuvant therapy.